Differences between inflammatory and catabolic mediators of peri‐implantitis and periodontitis lesions following initial mechanical therapy: An exploratory study. (12th September 2017) - Ghighi, M.; Llorens, A.; Baroukh, B.; Chaussain, C.; Bouchard, P.; Gosset, M.
Abstract : Background and Objective: The aim of this study was to analyze the differences in inflammatory and catabolic mediators expressed in peri‐implantitis compared to periodontitis lesions after non‐surgical therapy. Peri‐implantitis is associated with a faster rate of bone loss when compared with periodontitis, and peri‐implant non‐surgical therapy is ineffective to cure peri‐implantitis. This may be due to persistent inflammation in peri‐implantitis tissues after initial mechanical treatment. Material and Methods: Eleven patients with peri‐implantitis and 10 with severe chronic periodontitis received non‐surgical therapy. They were included at re‐evaluation (8 weeks) if they presented pocket depth ≥6 mm with bleeding on probing, and the indication for open flap debridement surgery. Connective tissues were harvested during surgery from diseased sites. Healthy gingiva were harvested during third molar extraction in a third group of healthy patients (n=10). Explants were incubated for 24 hours in media culture and the release of cytokines, chemokines, growth factors, osteoprotegerin, receptor activator of nuclear factor kappa‐B ligand (RANKL), matrix metalloproteinase and tissue inhibitors of matrix metalloproteinase (TIMP) in the conditioned media was analyzed by an exploratory multiplex immunoassay. When difference was found in the conditioned media, an immunohistochemistry was performed to compare expression in the tissues. Results: Connective tissues from non‐stabilized peri‐implantitis exhibited a distinct cytokine profile compared to periodontitis lesions that did not respond to initial therapy. Indeed, TIMP‐2 was significantly increased in media from peri‐implantitis ( P ≤.05). In addition, the in situ expression of TIMP‐2, interleukin‐10 and RANKL was also significantly increased in peri‐implantitis tissues ( P ≤.05). However, the ratio of RANKL/osteoprotegerin‐positive cells did not vary ( P ≥.05). Conclusion: This study suggests that peri‐implantitis and periodontitis connective tissues exhibit differences in response to non‐surgical treatment, which may contribute to a different pattern of disease evolution.